Utility of perioperative B-type natriuretic peptide in off-pump bypass surgery - Joshi, Dikshya; Guo, Zhi Gang (Nepalese Heart Journal, 2014)
Background and Aims: This study was performed to determine clinical relevance of perioperative B-type natriuretic peptide (BNP) in patients undergoing off-pump coronary artery bypass grafting. Methods: 145 consecutive patients undergoing off-pump coronary artery bypass grafting during 8-month period were enrolled in this study. The relationship between the plasma BNP and various clinical parameters was examined. Postoperatively their main clinical endpoints including requirement of mechanical ventilator support, length of intensive care unit stay and hospital stay was closely monitored. Results: Mean preoperative BNP levels were significantly higher in patients whose left ventricular ejection fraction was less than 0.50 (P